Current states in SNS junction for arbitrary concentrations of nonmagnetic impurities - Svidzinsky, A.V.; Sakhnyuk, V.E. (Condensed Matter Physics, 2000)
The boundary conditions are obtained for NS interface at the presence of arbitrary concentrations of nonmagnetic impurities. The current states in SNS junction are considered. The solution obtained for the current is analysed, in particular it was found out how the characteristic length of the current decreasing ξ₀ for pure superconductor turns to ξd for dirty one. A variant of the variational method, called the method of quasiorthogonality to asymptotics, is used to obtain the boundary conditions.